PENGARUH PERSEPSI, KOMPENSANSI DAN MOTIVASI TERHADAP KINERJA TUTOR - Jamil Jamil; Muin Muin (Kelola: Journal of Islamic Education Management, 2022)
This study shows the effect of tutors' perceptions, tutor's compensation, and their work motivation on the quality of face-to-face tutorial services (TTM) in the S1 PGSD Open University program. The approach used is quantitative using path analysis. The quality of tutorial services is the dependent variable while perception, compensation, and motivation are independent variables. The results of the study show that: (1) the higher the tutor's perception, the more influential it is on the quality of tutorial services (2) the higher the tutor's compensation, the more influential on the quality of tutorial services, (3) the higher work motivation, the higher the influence on tutorial quality services. These results confirm the importance of the perception of face-to-face tutors, tutor compensation affects work motivation mainly in terms of: (1) punctuality in carrying out assignments and (2) tutor's internal motivation getting better in carrying out their duties. UPBJJ- Makassar Open University must pay attention to the three elements related to the tutor's perception of the task, compensation as a reward received by the tutor after carrying out the task. UPBJJ in implementing face-to-face tutorials, tutors' perceptions of tutorial assignments in the PGSD program, compensation as financial rewards that are received on time will affect the motivation of the tutor's quality of work. PGSD Undergraduate Program students benefit from TTM services optimally if the tutor has a good perception of face-to-face tutorials, acceptable compensation and work motivation.